Pablo no fue cristiano : el mensaje original de un apóstol mal entendido - Eisenbaum, Pamela Michelle (Agora (Estella, Spain), 2014)
Reveals the historical Paul, not as the founder of a new Christian religion, but as a devout Jew who believed Jesus was the Christ who would unite Jews and Gentiles and fulfill God's universal plan for humanity.